The Effect of Post-discharge Telephone Training and Follow-up on Self-care Behaviors of Myocardial Infarction Patients - Masoud Khodaveisi; mehran salmani ghabeshi; Roya Amini; Leili Tapak (Hamadan University of Medical Sciences, 2022)
Background and purpose: Patients with myocardial infarction need to receive care and self-care ability. The aim of this study was to determine the effect of post-discharge education and follow-up on self-care behaviors of patients with myocardial infarction. Materials and Methods: In this quasi-experimental study, 116 patients with myocardial infarction were selected by convenience sampling method and randomly assigned to the two groups of control (n = 58) and intervention (n = 58). In the intervention group, a face-to-face training session was held first. Then telephone follow-up with training immediately after discharge, twice a week in the first month and once a week in the second month with the intervention group. The standard questionnaire of self-care behaviors in patients with myocardial infarction was used to collect information. SPSS software version 23 and descriptive statistics and Fisherchr('39')s independent and accurate t-tests were used to analyze the data. Results: The mean score of self-care in the intervention group in one month and two months after training compared to discharge time was 35.29 and 44.10 units, respectively. The results of LSD post hoc test showed that these differences were statistically significant (p <0.001). Using chi-square test, a statistically significant difference was observed between the frequency distribution of patients in the control and intervention groups in one month and two months after the intervention in terms of self-care. Conclusion: Due to its availability, the use of telephone follow-up can be used as a method to follow the training provided to patients.